2016
DOI: 10.1371/journal.pone.0160980
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Peptide, Selected from a Phage Peptide Library, Enhances Antitumor Activity of Lactaptin

Abstract: A recombinant analogue of lactaptin (RL2), a new potential anticancer molecule, induces apoptosis in cultured tumor cells. The tumor suppression efficacy of RL2 was shown against mouse hepatoma-1 cells and MDA-MB-231 human breast adenocarcinoma cells. The RL2-based therapeutic drug lactaptin is distributed evenly throughout the organism, which reduces its antitumor efficacy. In the current study, we obtained a genetic construct that allows production of the recombinant fusion protein T3-RL2, consisting of RL2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In Figure 3 shows fluorescence microscopy of cells incubated with bacteriophages 19C, 36C, 92, 26, selected on different phage libraries, in different screening systems. Phage M13, displayed the peptide YTYDPWLIFPAN previously selected for MDA-MB 231 cells, was taken as a negative control [ 5 ]. No significant differences were found in the efficiency of binding to cells of bacteriophages displayed the studied peptides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 3 shows fluorescence microscopy of cells incubated with bacteriophages 19C, 36C, 92, 26, selected on different phage libraries, in different screening systems. Phage M13, displayed the peptide YTYDPWLIFPAN previously selected for MDA-MB 231 cells, was taken as a negative control [ 5 ]. No significant differences were found in the efficiency of binding to cells of bacteriophages displayed the studied peptides.…”
Section: Resultsmentioning
confidence: 99%
“…For in vivo screening, we used the previously described methods [ 5 , 18 ], to wit. SCID mice with subcutaneously and orthotopic glioblastoma xenograft U-87 MG were injected into the tail vein with 300 μL of a phage peptide library with a concentration of 2 × 10 11 pfu/mL, diluted in saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More efforts have been made to obtain the targeting properties of lactaptin. Recently, Nemudraya et al [84] reported that two targeting peptides of T3(YTYDPWLIFPAN) and iRGD had the specificity for cancer cell and penetration to targeted cancer cell and tumor tissue. They were used to construct the fusion proteins T3-RL2, RL-iRGD-His and RL2-iRGD and evaluate the activity both in vitro and in vivo.…”
Section: T3mentioning
confidence: 99%
“…Resulting from the cytotoxic activity of milk fraction against various cancer cells in vitro, the proteolytic fragment of milk s k-Casein-lactaptin was purified and identified [2]. Recombinant analogue of lactaptin (RL2), covering the 57-134 amino acid sequence of k-Casein, was also efficient against tumors grafted onto mice [3][4][5][6]. The comparison of RL2 primary structure and the mechanism of its penetration into the cell suggests that it can be assigned to the cell penetrating peptide (supplementary materials) [7,8].…”
Section: Introductionmentioning
confidence: 99%